Cobertura de los servicios de internet de la empresa In.Planet S.A. en la ciudad de Babahoyo y su afectación en la rentabilidad - Guerrero Meza, David Josué (2017)
Some years ago, communication between people, especially at a distance, was quite complex, until a phenomenon that nowadays invaded the majority of the population in the world, the internet, began to emerge. Children, young people, even the elderly have made this world wonder something indispensable in their daily lives, without realizing it is everywhere, from when a cell phone is turned on until when a message is sent from whatsApp. Seeing that, everywhere, every moment, all people in one way or another use the internet, many people have opted to enter the internet market whether it is establishing a business as cyber, computer centers, selling mobile internet plans or in case of bigger companies providing internet to houses, offices and institutions, since they see in this business something very profitable. The present work emerged as a requirement for obtaining the title of Engineering in Accounting and Auditing awarded by the Technical University of Babahoyo, whose purpose was to study the coverage and its effect on the profitability of In.Planet SA, a provider of internet both residential as a business in the city of Babahoyo, using a descriptive-analytical methodology based on the collection of information through investigative tools such as interviews, made to both administrative and technical-operational personnel of the company. During the development of this case study was established the profitability in the months of February March and April of the year 2017 of In.Planet S.A. obtained by its limited coverage, it was also determined the profitability that could have had if the necessary management had been executed to be able to extend the coverage of this company in that city.